Presenting the Model and Prioritization of Lean Production Success Drivers (Case study: Iran Khodro Company) - Aryana Ravanbakhsh; Jalal Abdi (International Journal of Sustainability, 2024)
The purpose of the current research is to present a model and prioritize the drivers of lean production success (case study: Iran Khodro Company). The statistical population and statistical sample of this study consists of 20 experts (managers) of Iran Khodro production department. In this research, first, the most important key success factors of lean production were determined using the validity technique of the content validity ratio, then the interpretative structural modeling of the determined factors was discussed, and in the final part, the key success factors of lean production were prioritized using the OPA technique. The indicators of "senior management support and commitment, training and evaluation, use of lean concepts and techniques, kaizen team, employee participation, project consultant, reward system, lean suppliers, alignment with the organization's strategy, effective communication and lean customers" were identified, respectively.
Keywords: Iran Khodro company; Lean production success; lean customers; senior management